Pelaksanaan KKN Kemanusiaan Mahasiswi STIBA Makassar di Kelurahan Malunda, Kabupaten Majene - Zulfiah Sam; Saadal Jannah; Sartini Lambajo (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
Kelurahan Malunda is one of the areas affected by an earthquake measuring 6.2 on the Richter scale in West Sulawesi. Disaster survivors who survive in refugee camps are very vulnerable to post-disaster trauma, which is why the Humanitarian Community Service Program of STIBA Makassar aims to carry out the three principles of higher education by taking on the role of service and humanity in the Malunda area. The method of implementing the program begins by identifying the needs of the people in the affected areas using SOAR analysis which then results in several programs including social service, teaching the Koran with the dirosa method, Muslim taklim, memorizing the Koran for teenagers and a religious child festival. The results of the implementation of this program have had quite a positive effect on the community in dealing with post-earthquake psychological stress, as well as making a significant contribution to the quality of volunteer personnel in helping affected communities in the Malunda village.